Application of the Concept Circle in the Software GUI Matlab - Ratnawati, Sri; Kusno, Kusno; Kamsyakawuni, Ahmad (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2017)
Mathematics as a basic science has objects that are abstract, mathematical aimed at understanding the concept by providing the ability to reason logically, systematically, critical, careful and creative so that if the mathematics are taught using the book will be hard to accept students. Junior high school students in general are still difficulties in learning mathematics in particular on the material loop. Therefore, it needs the development of more interactive learning media and can help students in the learning process, one of them with the help of Software Graphic User Interface (GUI) Matlab. The concept of a circle is presented in the form of Software GUI Matlab so that students can use to understand the concepts of geometry with ease and be more independent, and help teachers to explain the concept of the circle in the learning process. The application of the concept of the circle in Matlab GUI Software is done by constructing a circle 1. Concept definition, 2. Elements of the circle, 3. The corners of the circle, 4. Relationships angle at the center of the circle and the angle of the circle, and 5. Nature tangent to the circle . Data construction concept of one to five are arranged in Matlab GUI program to produce instructional media in the form of software.